ANALISIS PENDAPATAN PEDAGANG TERNAK KAMBING DI KECAMATAN TIROANG KABUPATEN PINRANG - Iqra Allamal Insan; Muhammad Ishak (STIEM BONGAYA, 2020)
This study aims to project the potential of farming components in the agrosystem based on the type of goat farming in Pinrang Regency. Goats are pets that are sought after by residents in the District of Tiroang to increase their source of income and economic value. This will contribute to goat livestock entrepreneurs in various regions in Pinrang Regency. Based on an analysis of the measurement of the business costs of goat breeders enclose the fixed costs and variable costs. In addition, the specific target in this study is to analyze the income of goat farmers based on the scale of livestock ownership. The method used in this research is survey and observation methods.